Clinical features of post-COVID-19 period. Results of the international register “Dynamic analysis of comorbidities in SARS-CoV-2 survivors (AKTIV SARS-CoV-2)”. Data from 6-month follow-up - G. P. Arutyunov; E. I. Tarlovskaya; A. G. Arutyunov; Yu. N. Belenkov; A. O. Konradi; Yu. M. Lopatin; A. P. Rebrov; S. N. Tereshchenko; A. I. Chesnikova; H. G. Hayrapetyan; A. P. Babin; I. G. Bakulin; et al. (Российский кардиологический журнал)
Aim. To study the clinical course specifics of coronavirus disease 2019 (COVID-19) and comorbid conditions in COVID-19 survivors 3, 6, 12 months after recovery in the Eurasian region according to the AKTIV register. Material and methods.The AKTIV register was created at the initiative of the Eurasian Association of Therapists. The AKTIV register is divided into 2 parts: AKTIV 1 and AKTIV 2. The AKTIV 1 register currently includes 6300 patients, while in AKTIV 2 — 2770. Patients diagnosed with COVID-19 receiving in- and outpatient treatment have been anonymously included on the registry. The following 7 countries participated in the register: Russian Federation, Republic of Armenia, Republic of Belarus, Republic of Kazakhstan, Kyrgyz Republic, Republic of Moldova, Republic of Uzbekistan. This closed multicenter register with two nonoverlapping branches (in- and outpatient branch) provides 6 visits: 3 in-person visits during the acute period and 3 telephone calls after 3, 6, 12 months. Subject recruitment lasted from June 29, 2020 to October 29, 2020. Register will end on October 29, 2022. A total of 9 fragmentary analyzes of the registry data are planned. This fragment of the study presents the results of the post-hospitalization period in COVID-19 survivors after 3 and 6 months. Results. According to the AKTIV register, patients after COVID-19 are characterized by long-term persistent symptoms and frequent seeking for unscheduled medical care, including rehospitalizations. The most common causes of unplanned medical care are uncontrolled hypertension (HTN) and chronic coronary artery disease (CAD) and/or decompensated type 2 diabetes (T2D). During 3- and 6-month follow-up after hospitalization, 5,6% and 6,4% of patients were diagnosed with other diseases, which were more often presented by HTN, T2D, and CAD. The mortality rate of patients in the post-hospitalization period was 1,9% in the first 3 months and 0,2% for 4-6 months. The highest mortality rate was observed in the first 3 months in the group of patients with class II-IV heart failure, as well as in patients with cardiovascular diseases and cancer. In the pattern of death causes in the post-hospitalization period, following cardiovascular causes prevailed (31,8%): acute coronary syndrome, stroke, acute heart failure. Conclusion. According to the AKTIV register, the health status of patients after COVID-19 in a serious challenge for healthcare system, which requires planning adequate health system capacity to provide care to patients with COVID-19 in both acute and post-hospitalization period.